Daily Aftershock Forecasting Map Following the May 2008 Ölfus Earthquake (M6.3) in SW Iceland - Darzi, Atefe (Harvard Dataverse, 2022)
Data files and MATLAB scripts required to plot a daily aftershock seismicity forecasting map for earthquakes with Mw≥2 over the aftershock region in SISZ following the 29 May 2008 mainshock (Mw6.3). [generating Figure 7a]